Patient Characteristics and Results of Wilms Tumour Treatment - A Prospective Cohort Study from Pakistan - Farrah Bashir et al; Tariq Ghafoo; Shakeel Ahmed; Tanveer Tanveer (ziauddin University, 2024)
Background: Wilms tumour, also called nephroblastoma, is the most common renal malignancy in children, presenting, mostly as an abdominal mass. Chemotherapy and surgery are the mainstays of treatment depending upon the histopathology, risk group and stage of treatment. The aim of the study was to determine the treatment outcome of Wilms tumour in a tertiary care hospital in Pakistan. Methods: A Prospective cohort study was carried out at the Department of Pediatric Oncology, CMH-Rawalpindi, Pakistan. A cohort of patients with Wilms tumour, less than 16 years was followed prospectively from January 2012-2019. Statistical data were analysed by Chi-squared test and p-value<0.05 was considered statistically significant. Results: The study included 39(50.6%) males and 38(49.4%) females. Abdominal mass [70(90.9%)] was the most common problem, followed by abdominal pain, hematuria, and fever. In stage I, [34(44.2%)] patients were followed up for histopathology. n=64(83.1%) patients were divided into the intermediate-risk group and 13(16.9%) in the high-risk group. The patients [50(64.9%)] with the localized disease received vincristine and Actinomycin D for chemotherapy before the operative procedure, whereas, [10(13.0%)] for metastatic disease, received preoperative chemotherapy, including vincristine, actinomycin D, and doxorubicin. Furthermore, 3(3.9%) cases had treatment-related mortality, 15(19.5%) patients relapsed, and 11(14.3%) of them died later due to their advanced stage. Overall survival (OS) was 81.8% and event-free survival (EFS) was 76.6%. Conclusion: Stage of disease considerably affects treatment outcomes and survival. We acknowledge that low-stage Wilms tumour can be treated by early referral to a paediatric oncologist and surgeon. This intervention could improve survival of children with Wilms tumour. Keywords: Wilms Tumour; Treatment Outcome; Developing Country; Event Free Survival.